3D printable light-responsive polymers. Issue 3 (27th March 2017) - Roppolo, I.; Chiappone, A.; Angelini, A.; Stassi, S.; Frascella, F.; Pirri, C. F.; Ricciardi, C.; Descrovi, E.
Abstract : New photo-curable polymers suitable for 3D printing are here provided, exhibiting a mechanical light-responsivity upon laser irradiation. Azobenzene moieties are employed both as a dye component in the 3DP and as active groups, providing photo-mechanical responsivity. The incorporation of azobenzene units into polymeric matrices allows a reversible and controllable change of the Young's modulus of 3D printed micrometric structures. Abstract : New photo-curable polymers for 3D printing are provided, exhibiting mechanical light-responsivity upon laser irradiation. Azobenzene moieties are employed both as dyes in the 3D printing process and as active groups providing the desired light responsivity. The incorporation of azobenzene units into polymeric matrices allows a reversible and controllable change of the Young's modulus of a crosslinked micrometric structure. Depending on the temperature of operation, laser irradiation induces either a decrease (photo-softening) or an increase (photo-hardening) of the Young's modulus. Such a behaviour can be spatially controlled in order to locally modify the mechanical features of 3D printed objects such as microcantilevers.